Principles of the GETHIKA Approach (Green School, Tri Hita Karana, and Adiwiyata) as a Glocalization Model for Environmental Education in Schools - Nurul Mahruzah Yulia; Ganes Gunansyah; Neni Mariana; Hutkemri Zulnaidi; Rafika Putri; Muhammad Rusli; Suttrisno (Jurnal Pendidikan Sains Indonesia, 2026)
The core issue in environmental education at the elementary level is the strong emphasis on cognitive and technical aspects, leaving ecological awareness, spiritual values, and sustainable culture underdeveloped. This condition shows the urgency of an approach that links global sustainability values with local wisdom and institutional reinforcement. The global Green School movement promotes ecological culture through a whole-school approach, while the national Adiwiyata Program provides a policy framework for integrating environmental responsibility into Indonesian schools. At the local level, Tri Hita Karana from Penglipuran Village, Bali demonstrates how indigenous communities successfully maintain harmony between humans and nature. This research analyzes and formulates principles of glocalization-based environmental education by integrating global concepts (Green School), local values (Tri Hita Karana), and national policies (Adiwiyata). Using a literature study method, relevant sources from Scopus, SpringerLink, Sinta, ScienceDirect, and Google Scholar were reviewed. Thematic analysis and conceptual synthesis were conducted to understand the interconnectedness of Green School theory, Tri Hita Karana, Adiwiyata, and Roland Robertson’s glocalization framework. The study results in the GETHIKA model, which consists of seven principles: loving to learn from nature, educating and habituating green behavior, developing spiritual–ecological harmony, fostering cooperation among school communities, strengthening institutional governance, cultivating student leadership, and ensuring continuous real action.Overall, the GETHIKA model demonstrates how global ideas can be adapted through local wisdom and strengthened by national policies to shape a religious, participatory, and sustainable environmental education ecosystem in primary schools.